Short Selling Activities and Convertible Bond Arbitrage Empirical Evidence from the New York Stock Exchange - Werner, Sebastian P.; SpringerLink (Online service) (Wiesbaden : Gabler, 2010)
While some short sales are based on information or opinions about a firm$1 (Bs share price, this is not the case with many others. This statement coincides with the increasing use of arbitrage-related hedge fund strategies whereas it collides with public consensus that blames short sellers for decreasing stock prices and exacerbating the economic downturn. Sebastian Werner examines aggregate short sales and convertible bond arbitrage, which is a typical hedge fund strategy that involves a significant short position in the underlying stock of a long convertible bond position for hedging purposes. Focusing on events of extreme stock price changes and short selling activity, he provides insightful and new observations of the significant difference in the trading pattern, information content and resulting impact on stock returns of arbitrage- versus valuation-based short selling activities.s
Background and Empirical Predictions -- The Event Study Methodology -- Data, Full Sample and Variable Construction -- Difference in Abnormal Short Selling Activity Following Events of Large Positive Stock Price Changes -- Difference in Information Content of Extreme Short Selling Activity Events and the Impact on Stock Returns -- Overall Conclusion.
Keywords: Economics; Banks and banking; Economics/Management Science; Finance /Banking.